2021
DOI: 10.1186/s40693-021-00098-z
|View full text |Cite
|
Sign up to set email alerts
|

Macrofauna community patterns in a Chiloe Island channel used intensely for aquaculture: the ecological status of its benthic environment

Abstract: Background It is known that aquaculture may produce negative environmental effects on marine ecosystems. Southern Chile is one of the most important salmon and mussel-producing areas in the world. Here we assess the ecological status of benthic communities near farming centers in Caucahue Channel, Chiloe, which has been used intensely for salmon and mussel production for 30 years. Methods The macrofauna, sediments and water column were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…These results suggest that even in this short time-sampling period, the measured water column variables (in a multivariate approach) were sufficiently different to produce dissimilar environmental conditions between the two sections of Caucahué Channel. A study carried out in a similar period (June 21-24, 2014) [26] also found differences in environmental variables of the water column (temperature, salinity, dissolved oxygen, pH, among others, in a multivariate approach) between the two sections of the Caucahué Channel. It is important to note that our hydrographic sampling (June 19 and 30, 2014) was done in different transition phases from spring to neap tides.…”
Section: Spatial Dissimilarities Of Zooplankton and Environmental Var...mentioning
confidence: 81%
See 2 more Smart Citations
“…These results suggest that even in this short time-sampling period, the measured water column variables (in a multivariate approach) were sufficiently different to produce dissimilar environmental conditions between the two sections of Caucahué Channel. A study carried out in a similar period (June 21-24, 2014) [26] also found differences in environmental variables of the water column (temperature, salinity, dissolved oxygen, pH, among others, in a multivariate approach) between the two sections of the Caucahué Channel. It is important to note that our hydrographic sampling (June 19 and 30, 2014) was done in different transition phases from spring to neap tides.…”
Section: Spatial Dissimilarities Of Zooplankton and Environmental Var...mentioning
confidence: 81%
“…There is currently great interest in gathering more information about the ecological and physical-chemical characteristics of receiving ecosystems of salmon and mussel farms in southern Chile, with the aim of minimizing their environmental impacts and thus making them more sustainable [6,43,44]. Despite the global importance of Patagonian ecosystems for salmon and mussel production, there have been few studies on the potential environmental impact of the sum of aquaculture centers located in a geographic unit, and fewer still that include salmon and mussel farms together [26,44]. However, several studies have focused on the local effects (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In southern Chile, the burgeoning aquaculture industry has changed many coastal areas, making coastal habitats increasingly dynamic. For instance, godwits, as well as other shorebirds, exclusively forage in the supratidal mudflats located in coastal bays that are also used for the cultivation and harvesting of fish, shellfish, and algae [42][43][44] . The effects of such practices on shorebird communities are complex.…”
Section: Are Godwits Changing Their Migration Timing Adaptively?mentioning
confidence: 99%
“…Effects of aquaculture in the area were excluded, as the chosen model location is in the central gulf. Hernández-Miranda et al (2021) show local impact of aquaculture on environmental quality, with the highest impacts directly next to the coastal salmon farms. Bravo et al (2020) show significant regional downstream connectivity between aquaculture farms in the Inner Sea of Chiloé.…”
Section: Appropriatenessmentioning
confidence: 99%